Structure et floristique de la foret primaire a Dipterocarpacees de l'Est-Kalimantan - Sist, P.; Saridan, A. (1999)
Forest inventories conducted in Indonesia (Berau District, East Kalimantan) highlighted the main festures of the Dipterocarpaceae primary forest. Dipterocarpaceae species accounted for 25% of the stand (diameter > 10 cm), 50% of the basal area and 60% of the standing volume. In three primary forest control plots (total area 12 ha), 538 taxa were inventoried, with a mean of 182 different tree species per hetare. The Berau forest, in terms of stand density, basal area and standing volume, resembled Borneo forests, and specially Sabah forest. However, it had much higher proportion of Dipterocarpaceae species, which could be due to the absence of major climatic variations in this region. Although floristic variability within the stand has been explained by edaphic factors in previous studies, the present results indicated that forest dynamics are critical in determining the species composition of the forest